Realization of Actional Competence in Mood Types of Casual Conversation - Andi Tenry Lawangen Aspat Colle (Universitas Bengkulu, 2020)
This article aimed at explaining the realization of actional competence, which focused on language functions in the mood types of casual conversation. This study highlighted seven key areas of language functions proposed by Celce-Murcia et al. (2007), namely interpersonal exchange, information exchange, opinions, feelings, suasion, problems, and future scenarios. This study was descriptive qualitative research, where the participants were four students of a state university in Semarang. The finding of this study showed that among the speakers used mostly asking and giving information language function, which was realized in the form of declarative mood type. In other words, in this casual conversation among the speakers were trying to exchange information as much as possible. The present study has only investigated the realization of actional competence in students’ communication. Therefore, future researchers could investigate more deeply about the grammatical use of the students’ actional competence, especially in terms of language function. It is also crucial to include more participants with different backgrounds, such as formal situations, written discourse, or different cultures and gender.